Journal Economics, business & accountancy : THE TREND AND VARIATION OF INTELLECTUAL CAPITAL DISCLOSURE AT BANK INDUSTRIES IN EUROPE - Rafinda, Ascaryan , Agus Pramuka, Bambang :Indira Kusuma, Poppy Dian (PPPM Perbanas, 2013)
This study attempts to identify trend on the volume of Intellectual Capital (IC) disclosure, and measurevariation on the volume of IC disclosure on the annual report of banks that operate in Europe. It usespurposive sampling method, consisting of 6 banks with highest rank of market value in different countriesin Europe. The sample includes BNP Paribas (France), Banco Santander (Spain), Intesa Sanpaolo(Italy), UBS (Switzerland), Deutsche Bank (Germany), and ING Group (Netherlands).